Bioactive meroterpenoids and alkaloids from the fungus Eurotium chevalieri - Kanokmedhakul, Kwanjai; Kanokmedhakul, Somdej; Suwannatrai, Ruchiruttikorn; Soytong, Kasem; Prabpai, Samran; Kongsaeree, Palangpon (My University, 2011)
Five new meroterpenoids, chevalones A-D (1-4), aszonapyrone B (8), and a new sequiterpene alkaloid, eurochevalierine (5), together with four known compounds, sequiterpene (6), terpenoid pyrrolobenzoxazine named CJ-12662 (7), meroterpenoid, aszonapyrone A (9), and ergosterol were isolated from the fungus Eurotium chevalieri. The structures were established on the basis of spectroscopic evidence. The configurations of 1 and 5 were determined by X-ray analysis. The biosynthetic pathway of 1-3, 8, and 9 were proposed. Chemical transformation of aszonapyrone A (9) was also studied. Compounds 4, 5, and 7 exhibited antimalarial activity against Plasmodium falciparum, while 3, 5, and 7 showed antimycobacterial activity against Mycobacterium tuberculosis. In addition, compounds 2-7 showed cytotoxicity against cancer cell lines. © 2011 Elsevier Ltd. All rights reserved.
Keywords: Anticancer; Antimalarial; Antimycobacterial; Aszonapyrone; Chevalones; Eurochevalierine; Eurotium chevalieri; Meroterpenoids